Пошаговое объяснение:
a) m+3=-17.2+3=-14.2
6+m+3=9+m=9+(-17.2)=-8.2
6+m=6+(-17.2)=-11.2
б) k+2=-2.1+2=-0.1
4+k+2=6+к=6+(-2.1)=3.9
4+k=4+(-2.1)=1.9
в) m+1=-1.9+1=-0.9
2+m+1=3+m=3+(-1.9)=1.1
2+m =2+(-1.9)=0.1
e) a+2=-2.5+2=-0.5
3+ a+2=5+а=5+(-2.5)=2.5
3+a=3+(-2.5)=0.5
Пошаговое объяснение:
a) m+3=-17.2+3=-14.2
6+m+3=9+m=9+(-17.2)=-8.2
6+m=6+(-17.2)=-11.2
б) k+2=-2.1+2=-0.1
4+k+2=6+к=6+(-2.1)=3.9
4+k=4+(-2.1)=1.9
в) m+1=-1.9+1=-0.9
2+m+1=3+m=3+(-1.9)=1.1
2+m =2+(-1.9)=0.1
e) a+2=-2.5+2=-0.5
3+ a+2=5+а=5+(-2.5)=2.5
3+a=3+(-2.5)=0.5